The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/0040517519866931
|View full text |Cite
|
Sign up to set email alerts
|

Development of auxetic warp knitted fabrics based on reentrant geometry

Abstract: This paper reports a novel method to fabricate auxetic warp knitted fabrics on a tricot warp knitting machine based on a special structure design and knitting process. Three auxetic warp knitted structures were successfully developed and all of them were designed to form a reentrant hexagonal geometry to acquire an auxetic effect. To provide the fabrics with reentrant frames, elastomeric yarns and stiff yarns were used to form the elastic underlaps and stiff underlaps, respectively. While the elastic underlaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 33 publications
0
29
1
Order By: Relevance
“…Deriving v p (t), the acceleration curve formula a p (t) is shown in equation (20): According to the movement characteristics of guide bar lapping, h p ð0Þ ¼ 0, h p ðt f Þ ¼ h, v p ð0Þ ¼ 0, v p ðt f Þ ¼ 0, a p ð0Þ ¼ 0, a p ðt f Þ ¼ 0, these parameters are substituted to equation (16), equation (18), and equation ( 20) respectively. The constants…”
Section: Design Of the Shogging Velocity Curvementioning
confidence: 99%
See 2 more Smart Citations
“…Deriving v p (t), the acceleration curve formula a p (t) is shown in equation (20): According to the movement characteristics of guide bar lapping, h p ð0Þ ¼ 0, h p ðt f Þ ¼ h, v p ð0Þ ¼ 0, v p ðt f Þ ¼ 0, a p ð0Þ ¼ 0, a p ðt f Þ ¼ 0, these parameters are substituted to equation (16), equation (18), and equation ( 20) respectively. The constants…”
Section: Design Of the Shogging Velocity Curvementioning
confidence: 99%
“…f can be obtained. 16) and equation (18), the formulas of position trajectory h p (t) and velocity curve v p (t) for quintic polynomial can be calculated as follows:…”
Section: Design Of the Shogging Velocity Curvementioning
confidence: 99%
See 1 more Smart Citation
“…[ 4 ] This unusual behavior has also motivated various researchers to develop different types of auxetic fabrics. [ 2,5 ] To date, auxetic fabrics which have been developed can be roughly divided into auxetic woven fabrics, [ 6–12 ] auxetic‐knitted fabrics, [ 1,13–18 ] auxetic nonwoven fabrics, [ 19–21 ] and special auxetic fabric structures. [ 22 ]…”
Section: Introductionmentioning
confidence: 99%
“…Tensile tests were conducted after heat setting and it was concluded that the fabrics show auxetic behavior in a wide strain range. [ 16 ] Hu et al developed three types of knitted auxetic structures, i.e., foldable, rotating rectangle, and re‐entrant hexagon using computerized flat knitting technology. The results showed that Poisson's ratio effect varies with strain rate.…”
Section: Introductionmentioning
confidence: 99%